2020
DOI: 10.1002/hec.3977
|View full text |Cite
|
Sign up to set email alerts
|

The effect of health insurance on crime: Evidence from the Affordable Care Act Medicaid expansion

Abstract: Little evidence exists on the effect of the Affordable Care Act (ACA) on criminal behavior, a gap in the literature that this paper seeks to address. Using a simple model, we argue we should anticipate a decrease in time devoted to criminal activities in response to the expansion, because the availability of the ACA Medicaid coverage raises the opportunity cost of crime. This prediction is particularly relevant for the ACA expansion because it primarily affects childless adults, a population likely to contain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 77 publications
0
23
0
Order By: Relevance
“…The authors also report that the social‐cost savings associated with an additional local treatment facility, $4.2 million, are substantially greater than the annual costs of treatment in a facility, $1.1 million. Finally, He and Barkowski (2020) also examine the effects of health insurance on crime following the ACA Medicaid expansions using a sample of states and contiguous‐border counties from 2010 to 2016. The paper reports similar results to those presented in the current study, although the authors also report reductions for other types of crimes, including burglary, vehicle theft, robbery, and homicides, that are not robust with the inclusion of an additional three years of data.…”
Section: Policy Implications and Comparision To Related Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…The authors also report that the social‐cost savings associated with an additional local treatment facility, $4.2 million, are substantially greater than the annual costs of treatment in a facility, $1.1 million. Finally, He and Barkowski (2020) also examine the effects of health insurance on crime following the ACA Medicaid expansions using a sample of states and contiguous‐border counties from 2010 to 2016. The paper reports similar results to those presented in the current study, although the authors also report reductions for other types of crimes, including burglary, vehicle theft, robbery, and homicides, that are not robust with the inclusion of an additional three years of data.…”
Section: Policy Implications and Comparision To Related Literaturementioning
confidence: 99%
“…Without empirical evidence, it is unclear whether investments in healthcare lead to reductions in crime. Few studies have examined this relationship, most notably Wen, Hockenberry, and Cummings (2017), Bondurant, Lindo, and Swensen (2018), and He and Barkowski (2020). The former studies focus specifically on the link between treatment for SUD and criminal behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This assumption would be violated, for example, if there were responses among those who switched onto Medicaid from other sources of insurance, or if the benefits of health insurance affect households or communities. A growing literature documents responses consistent with diffuse benefits of Medicaid on, for example, financial outcomes (Hu et al (2016), crime (Vogler (2017), He (2018)), and hospital closures (Lindrooth et al (2018)); there is also little evidence of negative spillovers through congestion effects (Carey, Miller and Wherry (2018)). Large TOT estimates appear to be a feature of public insurance studies, suggesting that assessment of these programs should allow for benefits in the general population, and future research should more closely ex-amine the sources of gains from health insurance.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have found that Medicaid expansions are associated with a substantial reduction in crime (Wen et al 2017;Vogler 2018;Aslim et al 2019;He and Barkowski 2020).…”
Section: Introductionmentioning
confidence: 99%